Avaliação da efetividade de manejo da Estação Ecológica de Murici Alagoas. - Vasques, Henrique Carlos de Figueiredo (2009)
he creation of protected areas has been the main strategy for protecting natural and cultural resources in several countries including Brazil and has been much progress in recent years with the creation of new protected areas in several states of the federation including in Alagoas. However, to achieve biodiversity conservation the existence of protected areas is is not enough. It is also necessary to implement them and manage them properly so they can achieve their goals. Thus, it is necessary to make a systematic assessment of training deployment and quality of management of the protected area. This systematic assessment must serve as a basis for policy and strategies to increase the effectiveness of protected areas implementation. The Ecological Station (ESEC) of Murici is a conservation unit under full protection, created by decree w/n May 2001, in order to protect one of the largest remnants of Atlantic Forest in Northeastern Brazil. Within its boundaries is located the Station of sugar-cane Cross and Flowering Serra do Ouro (EFCSO), wich is linked to the Federal University of Alagoas (UFAL). The EFCSO is dedicated to scientific research of cross and flowering of sugar cane, aiming to increase its strength and productivity, EFCSO produces most of sugar cane varieties that are grown in Brazil. The fact that scientific experiments are conducted with sugar cane, an exotic species for the Atlantic Forest biome, has caused divergence of views between the Brazilian Institute of Environment and Renewable Natural Resources (IBAMA) and UFAL about the feasibility of these experiments within the ESEC. These conflicts had restrain the synergy between these two institutions face the common goal of sustainable development. The extent to which the partnership between the two institutions could contribute to the implementation of ESEC Murici is one of the objectives of this study. For that , the actual management effectiveness of ESEC Murici is compared with the effectiveness of implementation of a scenario in which this partnership is present. The prospective methods based on scenarios had been widely used for determining the degree of management effectiveness of conservation units. One of those methods is the Rapid Assessment and Priorization of Protected Area Management (RAPPAM), wich was developed by WWF (World Wide Fund for Nature). This method, being the most widely applied in the world and in Brazil, was adopted for this study because of its suitability for the assessment of conservation units under full protection. After the RAPPAM application, this study has showed the possibility of an increase of about 11% in the management effectiveness of the ESEC Murici after the implementation of the partnership.